Replacement Models with Minimal Repair - Tadj, Lotfi; Ouali, M.-Salah.; Yacout, Soumaya; Ait-Kadi, Daoud; SpringerLink (Online service) (London : Springer London, 2011)
Replacement Models with Minimal Repair is a collection of works by several well-known specialists on the subject of minimal repair in replacement policies. It gives an exhaustive list of minimal repair models for the effective planning of minimal repair and maintenance actions. Written in an engaging style, Replacement Models with Minimal Repair balances complex mathematical models with practical applications. It is divided into six parts that cover: mathematical modeling of minimal repair; preventive maintenance models and optimal scheduling of imperfect preventive maintenance activities; a new warranty servicing strategy with imperfect repair; mathematical models combining burn-in procedure and general maintenance policies; methods for parameters$1 (Bestimation of minimal repair models; and product support. Replacement Models with Minimal Repair is for anyone with an interest in minimal repair and its impact on maintenance policies and strategies. It is a particularly useful resource for researchers, practitioners, and graduate students.s
1. A Survey of Replacement Models with Minimal Repair -- 2. Information-based Minimal Repair Models -- 3. Minimal Repair Models with Two Categories of Competing Failure Modes -- 4. Preventive Maintenance Models: A Review -- 5. Optimal Schedules of Two Periodic Imperfect Preventive Maintenance Policies and Their Comparison -- 6. Warranty Servicing with Imperfect Repair for Products Sold with a Two-Dimensional Warranty -- 7. A Survey of Burn-in and Maintenance Models for Repairable Systems -- 8. Filtering and M-ary Detection in a Minimal Repair Maintenance Model -- 9. Efficient Product Support - Optimum and Realistic Spare Parts Forecasting.
Keywords: Engineering; System safety; Industrial organization (Economic theory).; Engineering; Quality Control, Reliability, Safety and Risk; Mathematical Modeling and Industrial Mathematics; Industrial Organization